2021
DOI: 10.1016/j.ijrobp.2020.11.066
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Ablative Radiation Therapy to All Lesions in Patients With Oligometastatic Cancers: A Phase 1 Dose-Escalation Trial

Abstract: Increasing evidence suggests that patients with a limited number of metastases benefit from SABR to all lesions. However, the optimal dose and fractionation remain unknown. This is particularly true for bone and lymph node metastases. Therefore, a prospective, single-center, dose-escalation trial was initiated. Methods: Dose-Escalation trial of STereotactic ablative body RadiOtherapY for non-spine bone and lymph node metastases (DESTROY) was an open-label phase 1 trial evaluating SABR to nonspine bone and lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The strengths of this prospective study include consistent and predefined patient selection, use of the state-ofthe-art gallium-68-PSMA-PET hybrid imaging as an initial staging procedure, consistent use of two predefined treatment schedules, and relatively long followup. Meanwhile, several clinical trials have been able to show safety and low risk for late complications of high-dose local aRT; nevertheless, there are also reports of serious side effects leading to death after aRT in oligometastatic patients [5,20,21]. Although the majority of patients in our trial had previously been irradiated, and some METs in 73% of patients were marginally or completely overlapping with the initial radiotherapy treatment volume, observed longterm toxicity was mild.…”
Section: Discussionmentioning
confidence: 68%
“…The strengths of this prospective study include consistent and predefined patient selection, use of the state-ofthe-art gallium-68-PSMA-PET hybrid imaging as an initial staging procedure, consistent use of two predefined treatment schedules, and relatively long followup. Meanwhile, several clinical trials have been able to show safety and low risk for late complications of high-dose local aRT; nevertheless, there are also reports of serious side effects leading to death after aRT in oligometastatic patients [5,20,21]. Although the majority of patients in our trial had previously been irradiated, and some METs in 73% of patients were marginally or completely overlapping with the initial radiotherapy treatment volume, observed longterm toxicity was mild.…”
Section: Discussionmentioning
confidence: 68%
“…Multiple recently published studies have demonstrated the significant benefit of localized therapy for oligometastatic RCC using ablative-intent SBRT in the treatment of metastases with improvements in overall survival, progression-free survival (PFS), and LC in the setting of acceptable treatment toxicity. [8][9][10][11] Furthermore, when specifically discussing treatment for oligometastatic RCC, studies suggest the benefit of ablative SBRT with improved outcomes. 12,13 In oligometastatic RCC patients who have prolonged survival, the importance of LC and decreasing morbidity of disease progression is even more pronounced.…”
Section: Discussionmentioning
confidence: 99%